Billion-dollar ball : a journey through the big-money culture of college football - Gaul, Gilbert M. (New York, New York : Viking, 2015)
"Over the past decade college football has not only doubled in size, but its elite programs have become a $2.5-billion-a-year entertainment business ... . In most cases, those windfalls are not passed on to the universities themselves, but flow directly back into their athletic departments. College presidents have been unwilling or powerless to stop a system that has spawned a wildly profligate infrastructure of coaches, trainers, marketing gurus, and a growing cadre of bureaucrats whose sole purpose is to ensure that players remain academically eligible to play. ... What are the consequences when college football coaches are the highest paid public employees in over half the states in an economically troubled country, or when football players at some schools receive ten times the amount of scholarship awards that academically gifted students do? Billion-Dollar Ball considers ... how an astonishingly wealthy sports franchise has begun to reframe campus values and distort the fundamental academic mission of our universities"--From publisher description.
Preface: Real University -- Gilded age of college football -- Unlikely charity known as college football -- Return on investment: the art of paying a coach $23 million not to coach -- Walking with Mr Baldwin: in the land of accidental students -- Why the south lost the war but wins at football -- How women's rowing saved college football: working the bar scene for recruits -- To have and have not: how college presidents fumbled reform -- Epilogue: Death star -- Note on sources -- Acknowledgments -- Index.
Includes index.
Keywords: College sports -- Moral and ethical aspects -- United States; College sports -- Corrupt practices -- United States; Football -- Corrupt practices -- United States; Football; National Collegiate Athletic Association; College sports -- Economic aspects -- United States